Beat structure in spectrally resolved four-wave mixing under crosslinear polarization in GaAs quantum wells - -, Suryadi; Ishihara, T.; Ohyama, H.; Kadoya, Y.; Yamanishi, M. (Elsevier, 2000)
The polarization dependence of beat structure in spectrally resolved four-wave mixing was investigated on GaAs multiple quantum wells. Under crosslinear polarization we observed a beating structure at higher energy region of the main spectral peak due to biexciton–exciton transition. The beat has a period of 0.95 ps and is constructive at delay time , which suggests the corresponding double Feynman diagrams to be of the same type. By shortening the central wavelength of the sub-ps laser, we observed the distinctive peak corresponding to the beat period. Even in GaAs system, which is generally believed to have a small biexcitonic effect, there are two effective 2-exciton states with well-defined energies which are required to describe the third-order optical nonlinearly.